Relationship between competency and spirituality with effective academic leadership among selected Malaysian public university academic leaders - Abu Samah, Siti Akmar (2014)
The purpose of this study is to examine the relationship between competencies,spirituality and the effectiveness of academicians as leaders of the institution of higher education. These are leaders who serve in varying hierarchy such as at course, programme, faculty and academic administrative levels. Research on leaders of higher institutions has been evolving on competencies in leadership, knowledge,skills and attitude. With the advent of global needs, challenges and requirements, inadequate competencies among leaders stifle to bring public universities to greater heights. Nevertheless, adding to competencies, spirituality is viewed as enhancing leadership effectiveness in the institution of higher education. Hence, the research renders for the following objectives to be achieved through further investigation specifically to examine whether there is significant relationship between the levels of competency, spirituality and academic leadership effectiveness perceived by academic leaders in the selected Malaysian universities; to determine the extent of relationship between competency and academic leadership effectiveness; to determine the extent of relationship between spirituality and leadership effectiveness among academic leaders in the selected Malaysian universities; to determine if there is statistically significant difference among academic leaders with regards to competency identified for academic leadership effectiveness and to determine if there is statistically significant difference among academic leaders with regards to spirituality identified for academic leadership effectiveness. Data have been collected through survey questionnaire conducted, with a sample of 180 academic leaders from the selected universities. The items of the questionnaire were chosen and adapted from previous studies. They were responded by selectedacademicians, those holding positions below the deputy dean level specifically those who are heads of programmes, courses or subjects that faculties offer as well as coordinators. Both descriptive and inferential analyses have been conducted. The validity and reliability of the instrument used were tested in a pilot study. Multiple regression approach has also been undertaken to analyse the data in order to answer the research questions. One-way analysis of variance (ANOVA), paired samples t test and Pearson Correlation, among others, were conducted to test the relationship of the variables being studied. In summary some crucial findings indicated the relationship that of competency level perceived by academic leaders stands at moderate level (60%) in relation to academic leadership effectiveness, while relationship of level of spirituality component perceived by academic leaders is ranked high (88.9%) in relation to academic leadership effectiveness. In addition, attitude has the most significant relationship on leadership effectiveness (Beta Coefficient .514) and human relationship (Beta Coefficient .808) has its most effect on the academic leaders to perform effectively. Academic leaders have to be aware of the challenges ahead when holding position with regards to attitude as a competency and human relationship as spirituality. Nonetheless, the other dimensions, namely competencies of leadership, knowledge, skills and spirituality, are not to be marginalized. Finally, several recommendations are proposed to enhance leadership in higher education in particular leadership development programmes and continuous education. The research outcome may also contribute to the process of selection with the proposal to utilize the knowledge and insights that have been conceptualized based on the findings. Therefore, the mechanism to conduct leadership search can assist the institution to choose and develop future leaders that can fill current academic leadership positions or for future replacement or succession. In conclusion, the relationship of these competencies identified complemented by spirituality have the slant in the basis for academic leader development that promotes continuous improvement for the institutions.